ETMR-16. Embryonal tumors with multi-layered rosettes: A case series in treatment for newly diagnosed children. (3rd June 2022) - Tran, Hung; Margol, Ashley; Cotter, Jennifer; Szymanski, Linda; O'Halloran, Katrina; Tamrazi, Benita; Michaiel, George; Christian, Eisha; Esfahani, Darian; Davidson, Tom Belle
Abstract: BACKGROUND: Embryonal tumors with multi-layered rosettes (ETMRs) are rare pediatric brain tumors with poorly defined prognostic features, standard of care treatments or outcome data. Recent data suggest that high-dose chemotherapy and radiotherapy is correlated with improved survival compared to chemotherapy alone. CASE DESCRIPTIONS: Four patients with newly diagnosed ETMRs were treated with 2 cycles of induction chemotherapy per PBTC-026 using isotretinoin, vorinostat, vincristine, cisplatin, etoposide, cyclophosphamide with added intrathecal topotecan. Second look surgery was performed if not in complete remission (CR). Consolidation was with three cycles of marrow-ablative chemotherapy (carboplatin and thiotepa) with autologous hematopoietic cell rescue followed by focal irradiation and 12 cycles of maintenance chemotherapy with intrathecal topotecan, vorinostat and isotretinoin. Patient 1 was a 3-year-old female with right parietal tumor, localized, and achieved gross total resection (GTR). Patient 2 was an 11-month-old male with posterior fossa tumor, localized, and achieved subtotal resection. Patient 3 was a 9-month-old female with posterior fossa tumor with near GTR, and metastasis to T12/L1 and L3/L4. [DTB1] [HNT2] Patient 4 was a 34-month-old male with a right frontal lobe tumor, localized and achieved GTR. Patient 1 is now 18 months from diagnosis and in CR. Patient 2 had second look surgery both after induction and consolidation but suffered neurologic injury to the brainstem which led family to decline further therapy. He is currently 14 months from diagnosis with stable residual disease. Patient 3 had local disease recurrence following radiation therapy at 10 months post diagnosis[DTB3] [HNT4], prior to maintenance. Patient 4 remains in CR at 13 months from diagnosis, currently in maintenance with vorinostat and isotretinoin but declined intrathecal topotecan. CONCLUSION: This case series adds to current knowledge of intensive multi-modal therapy for newly diagnosed ETMR. Further study to define standard optimal treatments in this high-risk group of patients is warranted.